Japan's ODA Contribution to the World Development - Nowik, Marcin (Oficjalna pomoc rozwojowa Japonii na rzecz światowego rozwoju, 2010)
Japan has been remaining one of the world's leaders in terms of Official Development Aid for years. The aim of the article is to indicate current Japan's engagement in world development aid, its origins and directions of further development. Japan's philosophy of ODA, rules of its implementation, geographical distribution and different forms of aid are discussed in the article. Finally Japan's involvement in ODA is compared with ODA donated by other DAC countries. The scale of Japan's assistance to development places the country fifth among largest donors, however, comparing aid to Japan's GNI moves the country to the last but one position among DAC members. What is more, Japan's ODA consists of larger percentage of loans and ties aid and lower percentage of grant element in comparison to other donors.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 56-66
Keywords: Japan; Official Development Assistance; DAC; aid